SMU announces new Dean for Yong Pung How School of Law - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
The Singapore Management University (SMU) announced today that it has appointed Professor Lee Pey Woan ( 李佩婉 ) as the new Dean of the SMU Yong Pung How School of Law (YPHSL), following an extensive and rigorous global search that started in August 2021.